LITERATURE REVIEW: OUTSOURCING AND OFFSHORING DEVELOPMENT TO ECONOMIC CONDITIONS IN COVID-19 PANDEMIC - Harto, Budi; Pramuditha, Panji (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
This research is based on the existence of a new trend in business activists, namely offshoring, where the system that is expected to use this new method is able to provide maximum business benefits by reducing costs to a minimum. Outsourcing cannot be separated from business activities as a third party in service, it is hoped that outsourcing can have a full impact on the company in order to minimize losses from less skilled employees. The Indonesian economy during the COVID-19 pandemic has become a new challenge for business activists recently. The method used in this research is (Systematic Literature Review) where the author makes a study in the results of journal articles that have been published domestically and internationally. The results of this review, produce a new reference, namely that outsourcing and offshoring in the economy in the era of the COVID-19 pandemic has a big impact, but it can be overcome by identifying problems, using low costs, as well as implementing effective, efficient and flexible.